2013
DOI: 10.4103/0189-6725.125449
|View full text |Cite
|
Sign up to set email alerts
|

Soave transanal one-stage endorectal pull-through in the treatment of Hirschsprung′s disease of the child above two-year-old: A report of 20 cases

Abstract: Soave transanal one-stage endorectal pull-through is safely feasible in children of more than two years of age. Laparoscopy may be necessary whenever there are difficulties in the pull-through.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This is significantly shorter than the average operative time in another study conducted in our department in patients of over 2 years age, who underwent a single-stage Soave endorectal pullthrough (240 minutes). [12] There was no significant intraoperative bleeding. This can be explained by the easier mucosal dissection during the neonatal period due to the presence of less adherent mucosa (no repeated episodes of enterocolitis), a less dilated colon above the aganglionic segment, that the mesentery and the colon are less substantial and easier to mobilize and that the blood vessels are easier to control.…”
Section: Discussionmentioning
confidence: 87%
“…This is significantly shorter than the average operative time in another study conducted in our department in patients of over 2 years age, who underwent a single-stage Soave endorectal pullthrough (240 minutes). [12] There was no significant intraoperative bleeding. This can be explained by the easier mucosal dissection during the neonatal period due to the presence of less adherent mucosa (no repeated episodes of enterocolitis), a less dilated colon above the aganglionic segment, that the mesentery and the colon are less substantial and easier to mobilize and that the blood vessels are easier to control.…”
Section: Discussionmentioning
confidence: 87%
“…Some paediatric surgeons documented that the role of laparoscopy in the interventional surgery for HD is limited to those with long aganglionic segment based on contrast enema study. [ 12 13 ] The reported advantages of laparoscopy for the management of HD cases were in agreement with those reported by Ksia et al .,[ 14 ] who retrospectively studied 20 patients older than 2 years who underwent a transanal Soave one-stage endorectal pull-through procedure for HD and concluded that laparoscopy may be necessary whenever there are difficulties in the pull-through. In our study, we used laparoscopy in short and long aganglionic segments.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ralls et al, redo pull-through patients of HD have worse stooling results than initial operations [ 27 ]. A study analyzed the growth outcomes of patients who underwent different pull-through methods; the Duhamel procedure (DP), Swenson procedure (SP), and TERPT showed the improvement of nutritional status was achieved in 21.2% of HD patients after TERPT, 14.3% post-Duhamel, and 5.9% following the Soave procedure [ 28 ]. In a study by Urushiara et al, it was shown that laparoscopic Z-shaped colorectal anastomosis for HD appears feasible and safe to perform with good results [ 29 ].…”
Section: Reviewmentioning
confidence: 99%